BIRD’S CHECKLIST OF MOENA CAÑO--CANTA GALLO ROAD, LORETO, PERU - AGUILAR-MANIHUARI, Ramón (2021)
This work presents the list of birds observed in the Moena Caño–Canta Gallo road in Loreto, Peru, which is in the peri-urban area of ​​Iquitos. This road is located on the right bank of the Itaya River and on the left bank of the Amazon River. The list was made with the records of casual bird watching outings since may 2017 until august 2021 and the records of virtual biological repositories were not considered. A total of 160 species were recorded, where the order Passeriformes represents 47% of the total species, the families Tyrannidae and Thraupidae are the most representative with 13% and 10% respectively. 158 species are categorized as "Least Concern", one as "Near Threatened" and one as "Vulnerable"; in addition, 23 are in appendix II of CITES, two in appendix III and none are considered in the national list of classification and categorization of threatened species. All the information collected in this work is important to fill information gaps related to the diversity and conservation status of the birds present in this part of the city of Iquitos.